An Analysis of Gender Equalities on Leadership in Local Government: The Case of the Mpumalanga Province, South Africa - Mokoena, S. K. (International Conference on Public Administration and Development Alternatives, 04 - 06 July 2018, Stellenbosch University, Saldahna Bay, South Africa, 2018)
This paper explores the issue of gender mainstreaming in government, with a particular reference to leadership positions in the South African Local Government sphere. It asserts that since democracy, South Africa has committed to the promotion of gender equality through legislation and policy initiatives. The paper is bias to leadership of the Local Government sphere, namely; the Offices of the Executive Mayors, Speakers and Municipal Managers in the Mpumalanga Province, South Africa for the period 2014 to date. Existing research argue that women under representation remains a persistent feature of politics internationally. However, gender equality is enshrined as a fundamental human right in Article 1 of the United Nation (UN) Charter stating that one of the purposes of the UN lies in the "… promoting and encouraging respect for human rights and for fundamental freedoms for all without distinction as to race, sex, language or religion". Thus, in view of the fact that the Sustainable Development Goal (SDG 5) – aims to achieve gender equality and empower all women and girls – this paper reflects on the practical realities and used the above-mentioned leadership portfolios in municipalities as a case study. The research design used on this paper was in accordance with the qualitative approach. It uses a narrative-analytical approach with a focus on descriptive analysis of variables and their impact on the effective implementation of gender equality. This approach is relevant in predicting a future framework for the future. However, the International Parliamentary Union has ranked South Africa as a 4th national parliament worldwide with 44.5 % of women parliamentarians. The outcomes point to the fact that women in these municipalities remain under-represented on strategic portfolios. Notwithstanding that South Africa has made general advances achieved in the public sector in this regard. Based on the outcomes above, it is evident that a particular attention still needs to be given to local government by the South African Government since it is a sphere that is closest to the people.
Journal article published in The 3rd Annual International Conference on Public Administration and Development Alternatives, 04 - 06 July 2018, Stellenbosch University, Saldahna Bay, South Africa
Keywords: Gender equalities; local government; Leadership; Leadership; Local government